Storage of embryos and in vitro development of embryonic axes in avocado - Edwin Antonio Gutierrez-Rodriguez; Renata Aparecida de Andrade; Rita de Cássia Panizzi; Syed Shaham Madni (Pesquisa Agropecuária Tropical)
The in vitro establishment of Persea americanaembryonic axes is critical for micropropagation and biotechnological applications, particularly following seed storage. This study aimed to evaluate the effects of seed storage duration and culture media composition on the in vitrodevelopment of P. americana (‘Toro Canyon’ and ‘Duke 7’ cultivars) embryonic axes in MS (Murashige & Skoog 1962), MSm (30 % of macronutrient reduction) or SHm (modified from Schenk & Hildebrandt 1972) media. Morphological parameters, including embryo and embryonic axis length, width and mass, were recorded. The in vitro assessments included survival, rooting and rosette formation. The experiment followed a completely randomized design, with four replicates. The ‘Duke 7’ seeds were longer and heavier than the ‘Toro Canyon’ seeds, but did not produce significantly larger embryos. Without storage, ‘Duke 7’ exhibited a higher survival in SHm and lower rooting in MS, while ‘Toro Canyon’ showed no significant differences in survival or development among the media, except for lower rooting in SHm. Storage duration and packaging type did not significantly affect survival or rooting percentages, but influenced the rosette explant formation, which was lower in MS. After six months of storage, the ‘Duke 7’ embryonic axes maintained 93 % of viability, with 31 % forming rosettes and 69 % rooting. These findings suggest that the storage viability depends more on culture medium composition than seed biometry.